On transformations involving generalized basic hypergeometric function of two variables - Yadav, R.; Purohit, S.; Vyas, V. (Rev. Téc. Fac. Ing. Univ. Zulia, 1970)
In the present paper, transformations for basic analogue of the Fox”™s H-function of one and two variables have been derived by the application of the q-Leibniz rule for the product of two basic functions. Some special cases involving a basic analogue of Meijer”™s G-function are also derived.